PENYEMBUHAN DALAM JEMAAT DITINJAU DARI SUDUT THEOLOGI - Rencan Carisma Marbun (Institut Agama Kristen Negeri Tarutung, 2019)
AbstractIn the Bible, we do not see the description of pain and healing as we haveencountered in the world of medicine. However, from a number of terms thebackground or meaning can be known. In the Old Testament, sickness is due to someone experiencing in their body something incomplete, or “badevents”. He does not experience normal bodily and mental life, perhaps due to infection, imbalance (harmony), or backward health, so he is called sick (holi). We see that healing is one of the responsibilities that humans can do for people who suffer from illness. The role of doctor and his remedybecomes and seems to indicate his responsibility towards the sufferingperson, who is deficient in reaffirming the people (cf. the term “hzk piel” in Jeremiah 30:21; 34: 4). In the New Testament, we do not find theimpression of illness arising as a sign of God's punishment, but instead inJesus’ ministry, He healed people, a sign of reestablishing the order of life with God (cf. Luke 4:18). Healing is generally an act or a way to heal the sick, and it can also be mentioned that healing is divine. Healing in Greek is called in the plural meaning the gifts of healing. The healing of miracles in the Gospel of John emphasizes the dynamic work of God and the sign (Greek: semeia) of His power. Disease is not only a result of sin, but also shows God’s work (9:3). So it is clear that healing miracles is not only valid individually, locally, or temporarily physical meaning, but also in general, provision and spiritual.Keywords: Healing, Congregation